MENCARI PENYEBAB AGRESIVITAS PELAJAR Hubungan Konsep Diri, Perhatian Orangtua, Afiliasi kepada Kelompok Nonagresif, dan Iklim Sekolah dengan Agresivitas - Basuki, Maryono (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The objective of this research is to study the relations between self concept, parentsâ attention, affiliation to nonaggressivegroup, school climate, and aggressivity of high school students in Jakarta. These five variables areseen from the perspective of educational technology. The research was conducted at SMU Darul Maâarif, SMUCendrawasih, and SMU Al Azhar during April-May-June 2011/2012 academic year), with 150 respondents (clusterrandom sampling). The result of the study indicated that: Self concept, parentsâ attention, affiliation to nonaggressivegroup, school climate, one by one and together influenced aggressivity. Group affiliation contribute aggressivityhigher than the other variables. Even school climate reduced aggressivity less then another variables,high influenced on improving affiliation to nonaggressive group. It is summarized that by: encouraging childrenaffiliate to nonaggressive group, improving self concept, raising parentsâ attention, and maintaining good schoolclimate, aggressivity can be reduced. It could be concluded that appropriate interactions will enhanced good behavior.This research, useing linier thinking, unsucceed to search the main cause of aggressivity, so in discussion,cybernetics method was applicated to reach supra-system and infra-system factors to discribe the cause of youthaggressivity in Jakarta/Indonesia.